Data on terrestrial ferns species richness, abundance, and functional traits in Mashpi Rainforest Biodiversity Reserve in the Ecuadorian Chocó - Salazar, Laura (2023)
This data paper summarizes the data of a first survey of ter restrial ferns at Mashpi Biodiversity Reserve, an Ecuadorian Chocó forest relict, one of the most biodiverse areas in the world. We established 10 permanent plots of 400 m2 dis tributed in two elevational levels (800 and 1000 m a.s.l.) to register all species per plot and the abundance per species. In addition, we measured two morphological leaf functional traits of the species. We include a file with three tables, the first one includes a species list with scientific names and vouchers. The second one includes the abundance of each species per plot. The third one contains measurements of the leaf length and leaf thickness of several leaf samples of 28 species, representing the leaf functional traits of the species. This article also includes a table with coordinates and eleva tions of the plots and five figures with information about the number of genus and species per family, geographic location of plots and, the methodology for data collection. These data can be useful for plant ecologists to assess future changes of